2021
DOI: 10.1038/s41598-021-95881-z
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of the spectral properties of dorsal wing scales with the phylogeographic structure of European male Polyommatus icarus butterflies

Abstract: The males of more than 80% of the Lycaenidae species belonging to the tribe Polyommatini exhibit structural coloration on their dorsal wing surfaces. These colors have a role in reinforcement in prezygotic reproductive isolation. The species-specific colors are produced by the cellular self-assembly of chitin/air nanocomposites. The spectral position of the reflectance maximum of such photonic nanoarchitectures depends on the nanoscale geometric dimensions of the elements building up the nanostructure. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Although peripheral territories still host different lineages (see also Arif et al [ 30 ]), our sampling has been confined to the central territory that corresponds with the area of the northern Palearctic lineage. Similar to the finding of Dincă et al [ 29 ], our previous work [ 23 ] that used microsatellites has found only minute genetic differences between Western and Central-Eastern European populations.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Although peripheral territories still host different lineages (see also Arif et al [ 30 ]), our sampling has been confined to the central territory that corresponds with the area of the northern Palearctic lineage. Similar to the finding of Dincă et al [ 29 ], our previous work [ 23 ] that used microsatellites has found only minute genetic differences between Western and Central-Eastern European populations.…”
Section: Methodssupporting
confidence: 89%
“…Working with butterflies with photonic nanoarchitectures in their wing scales with roles in sexual signalling [ 17 , 18 , 19 , 20 ] or camouflage [ 21 , 22 ], we faced the problem that the availability of museum samples is restricted, and in many interesting cases, destructive analyses are impossible. Moreover, the variables, which may influence the scale development and formation during the metamorphosis of the individual insect hitherto remain unexplored [ 18 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study on Polyommatus Latreille, 1804 subgenus Agrodiaetus Hübner, 1822 from 140 species in the tribe Polyommatini ( Polyommatinae ), only 26 species were found with brown dorsal coloration of the males, with all the others exhibiting different structural colours [44]. These colours, as they have a role in sexual selection of mates [45], are reproduced with very high precision over time periods of 100 years and distances of many thousands of kilometers [46,47]. And last, but not least, a further tuning possibility is offered by the combination of materials science methods like plasma etching of chitin and deposition of ZnO by ALD on the etched photonic nanoarchitecture [37].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, new morphometric techniques based on measurements of wing colour and its reflectance pattern have been tested for species identification and delimitation. For example, remarkably good correlations with genetic markers have been found for Lysandra bellargus and Polyommatus icarus ( Kertész et al 2021 ; Piszter et al 2021 ) and this colour morphometric technique can also be useful for discriminating between species of the Agrodiaetus subgenus.…”
Section: Introductionmentioning
confidence: 99%